Alcohol In Food According To Scientific And Islamic Perspective And Its Neuropsychiatry Effects - Nurul Jannah Abd Rahman; Ummu-Hani Abas; Nadrahtul Huda Misral (Usuli Faqih Research Centre PLT., 2024)
Indexed by MyCite